Nanoscale pathways for human tooth decay – Central planar defect, organic-rich precipitate and high-angle grain boundary. (March 2020) - Yun, Fan; Swain, Michael V.; Chen, Hansheng; Cairney, Julie; Qu, Jiangtao; Sha, Gang; Liu, Hongwei; Ringer, Simon P.; Han, Yu; Liu, Lingmei; Zhang, Xixiang; Zheng, Rongkun
Abstract: Understanding the pathways and mechanisms of human tooth decay is central to the development of both prophylaxes and treatments, but only limited information is presently available about the initiation of caries at the nanoscale. By combining atom probe tomography and high-resolution electron microscopy, we have found three distinct initial sites for human dental enamel dissolution: a) along the central dark line (CDL) within carbonated apatite nanocrystals, b) at organic-rich precipitates and c) along high-angle grain boundaries. 3D maps of the atoms within hydroxyapatite nanocrystallites in sound and naturally-decayed human dental enamel reveal a higher concentration of Mg and Na in the CDL. The CDL is therefore thought to provide a pathway for the exchange of ions during demineralization and remineralization. Mg and Na enrichment of the CDL also suggests that it is associated with the ribbon-like organic-rich precursor in amelogenesis. Organic-rich precipitates and high-angle grain boundaries were also shown to be more vulnerable to corrosion while low-angle grain boundaries remained intact. This is attributed to the lower crystallinity in these regions.